2009
DOI: 10.1007/978-3-642-10265-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Mobile Application Performance with Model–Driven Engineering

Abstract: Abstract. Future embedded and ubiquitous computing systems will operate continuously on mobile devices, such as smartphones, with limited processing capabilities, memory, and power. A critical aspect of developing future applications for mobile devices will be ensuring that the application provides sufficient performance while maximizing battery life. Determining how a software architecture will affect power consumption is hard because the impact of software design on power consumption is not well understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 15 publications
(16 reference statements)
1
14
0
3
Order By: Relevance
“…When the test operation is completed, the metrics are collected and stored (lines [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Figurementioning
confidence: 99%
“…When the test operation is completed, the metrics are collected and stored (lines [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Figurementioning
confidence: 99%
“…This DSML allows developers to specify their software architecture visually with respect to power consuming components, as shown in Figure 2. Prior work (Thompson et al, 2009;White et al, 2010;Turner et al, ) showed how the following components are often significant power consumers in mobile applications:…”
Section: Mobile Application Architecture Modeling and Power Consumptimentioning
confidence: 99%
“…We therefore hypothesized that SPOT could provide power consumption information to within 25% of the actual power consumption of WreckWatch and OpenGPSTracker. Based on prior work (Thompson et al, 2009;White et al, 2010;Turner et al, ), we also hypothesized that the components we chose represented the key factors in mobile application power consumption and would be adequate to provide this level of accuracy.…”
Section: Experiments 1: Empirical Evaluation Of Spot's Emulation Code mentioning
confidence: 99%
“…However CPS can also be seen in increasingly dynamic settings. Examples of mobile cyber-physical systems include applications to track and analyse Carbon Dioxide emissions [21], detect traffic accidents and provide situational awareness services to first responders [22], measure traffic [23], and monitor cardiac patients [24].…”
Section: Doorsmentioning
confidence: 99%